2019
DOI: 10.4097/kja.d.18.00163
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a mixture of 2.7% sorbitol-0.54% mannitol solution on blood coagulation: an invitro, observational healthyvolunteer study using rotational thromboelastometry (ROTEM)

Abstract: Background We investigated the effect of irrigation fluid on coagulation according to the hemodilution level using rotational thromboelastometry (ROTEM). Methods Venous blood was taken from 12 healthy volunteers and divided into four specimen tubes that were diluted to various levels (0%, 10%, 20%, and 40%) using an irrigation fluid composed of 2.7% sorbitol and 0.54% mannitol. Results Significant prolongation of clotting time was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…On the other hand, the CFT of all reagents was increased already after 20% dilution. These results are in line with previous reports and indicate that 20% dilution does not yet affect the initiation of coagulation (CT), but prolongs already the time to create a solid clot of 20 mm strength (CFT) [ 29 , 30 , 31 ]. Since the CFT, contrary to the CT, is highly dependent on sufficient platelet aggregation, these results indicate that hemodilution might have affected the concentration of platelets and their function [ 21 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the CFT of all reagents was increased already after 20% dilution. These results are in line with previous reports and indicate that 20% dilution does not yet affect the initiation of coagulation (CT), but prolongs already the time to create a solid clot of 20 mm strength (CFT) [ 29 , 30 , 31 ]. Since the CFT, contrary to the CT, is highly dependent on sufficient platelet aggregation, these results indicate that hemodilution might have affected the concentration of platelets and their function [ 21 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…That the TEM results on half‐filled samples were still within the references ranges in this study was consistent with the results from a previous study where blood was drawn from 12 healthy volunteers into citrate buffer containing tubes and then diluted with an irrigation fluid composed of 2.7% sorbitol and 0.54% mannitol . Results showed that for dilution levels of up to 30% volume irrigation fluid most TEM results were within the reference range, whereas at a dilution of 40% most were not within the reference range .…”
Section: Discussionsupporting
confidence: 91%
“…70 Additionally, contamination of hemostasis samples with a glucose-containing solution found diluting whole blood, with increasing glucose concentration ( P < .0001) drastically prolonged clot formation time, which further supports our findings. 71 Although hyperglycemia is associated with enhanced thrombin formation, platelet activation, and resistance to lysis, in reality, it is likely that the combination of increased fibrinogen and thrombin concentrations, in addition to fibrinogen glycation, is what drives clot formation and causes a prolonged clotting time with densely formed fibrin fibers. Although not conducted in this study, a lower d f from LSM data likely signifies thrombus formation that is more resistant to lysis and could be used to explain the increased clotting risk in the hypercoagulable state of DM with additional experimentation.…”
Section: Discussionmentioning
confidence: 99%